Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/bdrb.20051
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal migration is transiently delayed by prenatal exposure to intermittent hypoxia

Abstract: BACKGROUND: Neonatal neurodevelopment is influenced by a variety of external factors, although the mechanisms responsible are poorly understood. Prenatal hypoxia, from physiological or chemical sources, can have no discernible effect, or can result in a broad spectrum of abnormalities. METHODS: To mimic some of the maternal effects of smoking, we developed a model that investigates the effects of intermittent hypoxia (IH), with or without concurrent nicotine in timed pregnant Sprague-Dawley rats. RESULTS: We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Recent evidence suggests that intermittent hypoxia may affect proteins involved in neuronal migration and that nicotine exacerbates this effect [31].…”
Section: Evidence From Animal Modelsmentioning
confidence: 99%
“…Recent evidence suggests that intermittent hypoxia may affect proteins involved in neuronal migration and that nicotine exacerbates this effect [31].…”
Section: Evidence From Animal Modelsmentioning
confidence: 99%
“…Recent studies using DNA microarrays have shown that gestational nicotine exposure affects gene expression associated with cell adhesion and cell death/survival in the brains of adolescent rats (Cao et al, , 2013Wei et al, 2011). Although the effect of nicotine on neuronal migration has not yet been studied in detail, it has been reported that exposure to nicotine with intermittent hypoxia during gestation inhibited neuronal migration while nicotine alone (without intermittent hypoxia) had no effect (Zechel et al, 2005). These previous results are consistent with our present findings (Figure 2 and Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…There were corresponding changes in the peroxisomal antioxidant enzyme catalase, as well as the tyrosine kinase c-Abl that has been shown to control both the stability and activity of catalase [291,292]. Cell cycle proteins, Cdk5 and p25, and cytoskeletal proteins, neurofilament H and F-actin, involved in neuronal migration were altered by the hypoxia [290].…”
Section: Hypoxiamentioning
confidence: 99%
“…It has been hypothesized that embryos may conserve ATP by reducing cellular proliferation and, consequently, hypoxia may cause growth retardation in embryos [289]. Consistent with this view because cigarette smoking has been shown to induce growth-retarded newborns, a rat model of exposure to intermittent hypoxia has been developed to mimic the effects of smoking [290]. The rat offspring were not found to have decreased weights at birth, but developed long term diminished body weights and transient delay in neuronal migration during the neonatal period.…”
Section: Hypoxiamentioning
confidence: 99%